E-Portofolio Berbasis Project Based Learning Terintegrasi Googledoc pada Matakuliah Media Pembelajaran - Arini Rahmadana (Jurnal Syntax Transformation, 2022)
Information technology, advancing rapidly in the 21st century, has a significant effect on all aspects of life. This research is a classroom action research designed to implement the google doc integrated project-based learning model to produce learning media products using research and development methods. This study aimed to determine the use of an e-portfolio based on Google doc Integrated Project-Based Learning in the Learning Media Course. After the learning process with the PJBL model, the results of this study were carried out in groups, and it was found that five groups of students succeeded in producing media products